KAPASITAS SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI SERTA PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN KOPERASI - Hairul Anam (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
The purpose of this study is to determine whether the capacity of human resources, utilization of information technology and internal control affect the quality of financial reports. The sample in this study was forty-seven respondents who were taken from cooperatives registered at the Department of Cooperatives, Small and Medium Enterprises and Industry of Balikpapan City. The sampling method used purposive sampling method and the analysis tool used multiple linear regression analysis. The results showed that the capacity of human resources and internal control did not affect the quality of the cooperative's financial statements, while the use of information technology had a significant effect on the quality of the cooperative's financial statements.